E-Learning: can it help the education in Bangladesh? - Pathan, Al-Sakib Khan; Hassan, Md. Mehedi (2005)
E-Learning could be defined as instructional content or learning experiences delivered or enabled by the current advanced computer and other technologies. In many cases, especially in the developed countries, adoptions of E-Learning alongside the traditional classroom learning have shown promise for effective human learning. Being a developing country, adoption of E-Learning in Bangladesh stumbles, where many other factors come into play side by side the technological limitations. The intent of this paper is to identify the prospects and challenges for launching E-Learning in larger scale in Bangladesh. We also discuss how human learning process could be influenced by E-learning strategies and why E-Learning could be helpful for a country like Bangladesh.